2004
DOI: 10.1515/hf.2004.074
|View full text |Cite
|
Sign up to set email alerts
|

On-line study of lignin behaviour in dilute alkaline solution by the SEC-UV method

Abstract: The dynamic method for monitoring ionisation of the lignin functional groups in a 0.1 N NaOH solution at ambient temperature by means of the SEC technique with multiwave UV detection was performed. An increase in absorbance at 210, 278, 304, 320 and 350 nm was examined to reveal the ionisation dynamics in respect to functional groups’ acidity; that is, carboxyl groups, carbonyl- and double-bond conjugated phenol hydroxyls. A distinctive response of absorbance at 210 and 278 nm on the ionisation of carbonyl- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…A UV wavelength of 320 nm was chosen for the analysis of lignins, because virtually no signal was obtained from the degraded catalyst at this wavelength. Lignin, by contrast, provided a signal at 320 nm, which corresponds to the wavelength reflecting the concentration of aromatic carboxylic acids and a-carbonyl groups (Bikova et al 2004). Hence, a certain error can be expected if the oxidation leads to the formation of additional carbonyl groups preferably in a fraction of the product mixture.…”
Section: Methodsmentioning
confidence: 99%
“…A UV wavelength of 320 nm was chosen for the analysis of lignins, because virtually no signal was obtained from the degraded catalyst at this wavelength. Lignin, by contrast, provided a signal at 320 nm, which corresponds to the wavelength reflecting the concentration of aromatic carboxylic acids and a-carbonyl groups (Bikova et al 2004). Hence, a certain error can be expected if the oxidation leads to the formation of additional carbonyl groups preferably in a fraction of the product mixture.…”
Section: Methodsmentioning
confidence: 99%
“…To some extent this could be connected with the formation of so called "pseudolignin" due to the grafting of intermediate products of destruction of carbohydrates on lignin macromolecules and formation of heteroaromatic cycles [27,28]. The presence of such heteroaromatic impurities was clearly shown using multi-wave UV-vis detection during size exclusion chromatography (SEC) analysis of softwood kraft lignin, wheat straw soda lignin and soluble fractions of lignin obtained by percolation hydrolysis [27,29,30].…”
Section: Chemical Composition and Functionality Of Lhrsmentioning
confidence: 99%
“…A number of studies have shown that high chemical heterogeneity of lignin, including differences in lignin macromolecule chemical structure, functionality and molecular mass distribution, can turn impractical its applicability as antioxidant in targeted systems (Ponomarenko et al, 2015;Bikova et al, 2004). Recently, it was reported different strategies to obtain homogeneous lignin fractions with antioxidant activity, such as acid precipitation (dos Santos et al, 2014;Ma et al, 2013;Faustino et al, 2010) and sequential solvent fractionation (Ponomarenko et al, 2015;Cui et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%